O potencial empreendedor dos microempresários do Shopping Popular de Londrina - Avanzi, Jorge (2006)
One of the characteristics of successful entrepreneurs is vision. Guided by it, the entrepreneur directs its activities involving the necessary people and resources in the search of the accomplishment of its enterprise objectives. The present study analyses the enterprising potential of the micro-entrepreneurs of the Popular Shopping Center of Londrina and its business pretensions with regard to its establishments. To measure the enterprising potential, a portuguese version of the Carland Entrepreneurship Index - CEI (measurement instrument of enterprising potential) was used. After that, separated in groups of high and low enterprising potential, the business pretensions of each group were analyzed. The research is exploratory and interviewed 95 storekeepers from the Popular Shopping Center in the month of May of 2006. As result, the sample presented CEI indexes varying from 8 to 23, fitting the interviewed in the classifications "Micro Entrepreneur" and "Entrepreneur". In the comparison between "Micro Entrepreneur" and "Entrepreneur" differences relating the business pretensions of the storekeepers to their establishments weren't identified. The sample was divided in two groups, one formed by those facing the growth of their business and other formed by those facing the Status Quo. The statistics tests don't identified significant differences between the CEI indexes of both groups. However, the study revealed that the Carland Entrepreneurship Index - CEI questions about propensity to the risk were most punctuated inside the group of the interviewed that are facing the growth of their business.